Analisis Estimasi Waktu Proses Pembuatan Roda Gigi Miring Untuk Gearbox Mesin Kertas - Rahelia, Vira Deandra; Oleh, Oleh; Anjani, Ratna Dewi (Jurnal Ilmiah Wahana Pendidikan, 2023)
Machines have a very important role to support and improve human life for the better, therefore before machines are made, many things must be considered. including: the working principle of the machine, the materials used, what the best design looks like, and many others. This research is to find out the process of making bevel gears in a gearbox and knowing the estimated time for making oblique gears. From the research results, it was found that the process of making these gears was making technical drawings of the gear, selecting the material to be used, the process on the lathe, the process on the hobbing machine, and the hardening process. The result of calculating the estimated time for making gears based on theory is that the feeding time for 1 tooth with an average weight of 3.15 kg takes 12 minutes. The total from installation to finished goods takes 4 hours 22 minutes, and the results of calculations based on the field are that the feeding process per 1 tooth takes 13 minutes. The total time from installation to finished goods takes 5 hours.